Keynes and the historical specificity of institutions: a response to Rod O'Donnell. Issue 4 (31st January 2019) - Hodgson, Geoffrey M.
Abstract: This is a response to the criticism by Rod O'Donnell of the account of Keynes' notion of a general theory in the book How Economics Forgot History (Hodgson, 2001). Several points of full agreement are noted, including the fact that Keynes' work contains much discussion of historically specific institutions, including the financial and market institutions of modern capitalism. But it is argued here that even copious discussion of historically specific institutions is insufficient to indicate an adequate understanding or conceptual appreciation of historical periodisation or evolution, as developed in various ways by Karl Marx, the German historical school and the original American institutionalists. Keynes' General Theory is best understood as a theory of modern capitalism. But Keynes did not have sufficient acquaintance with these historically oriented schools of thought to even define the concept of capitalism, or to make that specific historical association clear.